Acute effect of static stretching on power output during concentric dynamic constant external resistance leg extension - Yamaguchi, T.; Ishii, K.; Yamanaka, M.; Kazunori, Y. (The Journal of Strength and Conditioning Research, 2006)
The purpose of the present study was to clarify the effect of static stretching on muscular performance during concentric isotonic (dynamic constant external resistance [DCER]) muscle actions under various loads. Concentric DCER leg extension power outputs were assessed in 12 healthy male subjects after 2 types of pretreatment. The pretreatments included (a) static stretching treatment performing 6 types of static stretching on leg extensors (4 sets of 30 seconds each with 20-second rest periods; total duration 20 minutes) and (b) nonstretching treatment by resting for 20 minutes in a sitting position. Loads during assessment of the power output were set to 5, 30, and 60% of the maximum voluntary contractile (MVC) torque with isometric leg extension in each subject. The peak power output following the static stretching treatment was significantly (p < 0.05) lower than that following the nonstretching treatment under each load (5% MVC, 418.0 +/- 82.2 W vs. 466.2 +/- 89.5 W; 30% MVC, 506.4 +/- 82.8 W vs. 536.4 +/- 97.0 W; 60% MVC, 478.6 +/- 77.5 W vs. 523.8 +/- 97.8 W). The present study demonstrated that relatively extensive static stretching significantly reduces power output with concentric DCER muscle actions under various loads. Common power activities are carried out by DCER muscle actions under various loads. Therefore, the result of the present study suggests that relatively extensive static stretching decreases power performance.